Pengembangan Sistem Penandatanganan Digital pada Layanan Sertifikasi Elektronik Berbasis Public Key Infrastructure - Diaz Seno Hutomo; Wakhid Kurniawan (LPPM Universitas Bhinneka Nusantara, 2026)
Digital transformation in the modern era shifts documents from physical to electronic formats, improving administrative efficiency but simultaneously introducing new vulnerabilities like identity fraud, content manipulation, and signature repudiation. To mitigate these risks, this research successfully designs a robust digital certification service system ensuring data integrity, sender authenticity, and non-repudiation. The methodology adopted an experimental observational approach through software development based on the Waterfall model. It was evaluated using thirty PDF certification documents on a server environment running Go 1.26, an AMD Ryzen 7 4700 processor, and 16 GB RAM. The system architecture integrates a React.js frontend for visual interaction and a Golang backend focused purely on cryptographic computation. Its security infrastructure employs a Public Key Infrastructure (PKI) model, integrating the 2048-bit RSA algorithm for asymmetric key encryption and SHA-256 for document identity hashing. Testing revealed the signature placement mechanism succeeded with an average single-signature execution time of 8.05 ms, displaying zero failures across all documents. Employing binary byte structure analysis and the Force Binary Download method successfully eliminated false positive anomalies caused by browser metadata modifications, which were independently validated via OpenSSL and Python scripts in Google Colab. In conclusion, this electronic certification service platform effectively facilitates real-time document verification, provides absolute protection of data integrity, and ensures the validity of authentication in accordance with Indonesian legal standards for electronic transactions.